The bartender's best friend : a complete guide to cocktails, martinis, and mixed drinks / Mardee Haidin Regan - Regan, Mardee Haidin
Congratulations! You've just discovered the ultimate bartender's guide that's up-to-date, practical, and easy-to-use. Inside you'll find recipes for hundreds of delicious cocktails and mixed drinks, plus step-by-step directions for making virtually every contemporary and classic drink ordered at bars and restaurants today - from an A.B.C. to a Zorbatini.